A REVIEW ON THE BIOMEDICAL APPLICATIONS OF ALUMINA - Harith Hasoon Al-Moameri; Zainab Majid Nahi; Dina Raheem Rzaij; Noor T. Al-Sharify (Journal of Engineering and Sustainable Development, 2020)
This review presents the composition, structure, mechanical characteristics, and applications of alumina (aluminum oxide) in biomedical. Alumina used for implant manufacturing is either single-crystal sapphires or high density and quality polycrystalline. The major sources of highly-purity alumina are organic corundum and bauxite. Like any other brittle component, polycrystalline alumina's mechanical characteristics are largely dependent on grain size and porosity distribution. It was shown that, due to slowed subcritical crack production, the fatigue intensity of alumina could be increased above the crucial pressure due to the presence of liquid. Due to its high inertness, that results in outstanding biocompatibility and tissue nonsensitization, alumina has significant benefits over other products in biomedical uses. Just like in artificially joints and teeth, the higher compressive strength than tensile strength allows it more efficient for compressive loadings. There were some attempts for coating alumina on steel substrates in order to benefit of its outstanding biocompatibility and to resist metal oxidation.